2021
DOI: 10.1371/journal.pbio.3001442
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, taxonomy, and evolution of archaeal viruses of the class Caudoviricetes

Abstract: The archaeal tailed viruses (arTV), evolutionarily related to tailed double-stranded DNA (dsDNA) bacteriophages of the class Caudoviricetes, represent the most common isolates infecting halophilic archaea. Only a handful of these viruses have been genomically characterized, limiting our appreciation of their ecological impacts and evolution. Here, we present 37 new genomes of haloarchaeal tailed virus isolates, more than doubling the current number of sequenced arTVs. Analysis of all 63 available complete geno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 101 publications
7
90
0
Order By: Relevance
“…The diversification of Nucleocytoviricota before LECA is indeed supported by the RNA polymerase phylogenetic tree including both viral and cellular enzymes (Guglielmini et al 2019). Moreover it has been suggested that Caudoviricetes , which also infect archaeal hosts (Liu et al 2021), have diverged even prior to the emergence of LUCA (Krupovic et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The diversification of Nucleocytoviricota before LECA is indeed supported by the RNA polymerase phylogenetic tree including both viral and cellular enzymes (Guglielmini et al 2019). Moreover it has been suggested that Caudoviricetes , which also infect archaeal hosts (Liu et al 2021), have diverged even prior to the emergence of LUCA (Krupovic et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Biologists describe them as natural parasites (or predators) of bacteria and associate them with maintaining the balance of microorganisms on Earth (Wittebole et al, 2014). Tailed phages of the class Caudoviricetes including podovirus, myovirus, and siphovirus (Liu et al, 2021), and the polyhedral Microviridae family are usually associated with phage therapy applications (Supplementary Figure 1; Harper and Enright, 2011;Lin et al, 2017). Scientists attribute the phages' antibacterial activity to their well-established life cycle (lytic or lysogenic; Supplementary Figure 2).…”
Section: Phages In Seamentioning
confidence: 99%
“…HF2 is a myovirus belonging to the species Haloferacalesvirus HF1, within the genus Haloferacalesvirus (family: Hafunaviridae, previously Myoviridae) [1]. It is lytic and can infect two species of extremely halophilic archaea, Halorubrum saccharovorum and Halorubrum coriense [2].…”
Section: Introductionmentioning
confidence: 99%
“…The modular gene organization in haloferacalesviruses is well conserved [1,6]. Genes are organized as modular units in two genomic arms so that most genes are directed towards the centre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation